Massive gastrointestinal hemorrhage. Due to a duodenal vascular malformation.: lts treatment by superselective embolization. - Tiscornia, Eduardo; Delgado, Alicia; Lerena, Ana; Bounous, Mario; Bermúdez, Jorge; Sojo, Enrique (Cirugía del Uruguay, 1985)
The origin of a massive upper gastrointestinal bleeding is sometimes dificull to know. lt is necesary to perform angiography when endoscoPY fails in the diagnosis and localization of the lesion. We present a case of gastrointestinal bleeding due a congenital arteriovenous malformation of duodenum. Treatment by transcatheter en::ibolization is an effective method to control gastrointestinal hemorrhage.